Renal and Vascular Effects of Combined SGLT2 and Angiotensin-Converting Enzyme Inhibition. Issue 6 (11th July 2022) - Lytvyn, Yuliya; Kimura, Karen; Peter, Nuala; Lai, Vesta; Tse, Josephine; Cham, Leslie; Perkins, Bruce A.; Soleymanlou, Nima; Cherney, David Z.I.
Abstract : Background: The cardiorenal effects of sodium-glucose cotransporter 2 inhibition (empagliflozin 25 mg QD) combined with angiotensin-converting enzyme inhibition (ramipril 10 mg QD) were assessed in this mechanistic study in patients with type 1 diabetes with potential renal hyperfiltration. Methods: Thirty patients (out of 31 randomized) completed this double-blind, placebo-controlled, crossover trial. Recruitment was stopped early because of an unexpectedly low proportion of patients with hyperfiltration. Measurements were obtained after each of the 6 treatment phases over 19 weeks: (1) baseline without treatment, (2) 4-week run-in with ramipril treatment alone, (3) 4-week combined empagliflozin-ramipril treatment, (4) a 4-week washout, (5) 4-week combined placebo-ramipril treatment, and (6) 1-week follow-up. The primary end point was glomerular filtration rate (GFR) after combination treatment with empagliflozin-ramipril compared with placebo-ramipril. GFR was corrected for ramipril treatment alone before randomization. At the end of study phase, the following outcomes were measured under clamped euglycemia (4 to 6 mmol/L): inulin (GFR) and para-aminohippurate (effective renal plasma flow) clearances, tubular sodium handling, ambulatory blood pressure, arterial stiffness, heart rate variability, noninvasive cardiac output monitoring, plasma and urine biochemistry, markers of the renin-angiotensin-aldosterone system, and oxidative stress. Results: Combination treatment with empagliflozin-ramipril resulted in an 8 mL/min/1.73 m 2 lower GFR compared with placebo-ramipril treatment ( P =0.0061) without significant changes to effective renal plasma flow. GFR decrease was accompanied by a 21.3 mL/min lower absolute proximal fluid reabsorption rate ( P =0.0092), a 3.1 mmol/min lower absolute proximal sodium reabsorption rate ( P =0.0056), and a 194 ng/mmol creatinine lower urinary 8-isoprostane level ( P =0.0084) relative to placebo-ramipril combination treatment. Sodium-glucose cotransporter 2 inhibitor/angiotensin-converting enzyme inhibitor combination treatment resulted in additive blood pressure–lowering effects (clinic systolic blood pressure lower by 4 mm Hg [ P =0.0112]; diastolic blood pressure lower by 3 mm Hg [ P =0.0032]) in conjunction with a 94.5 dynes × sex/cm 5 lower total peripheral resistance ( P =0.0368). There were no significant changes observed to ambulatory blood pressure, arterial stiffness, heart rate variability, or cardiac output with the addition of empagliflozin. Conclusions: Adding sodium-glucose cotransporter 2 inhibitor treatment to angiotensin-converting enzyme inhibitor resulted in an expected GFR dip, suppression of oxidative stress markers, additive declines in blood pressure and total peripheral resistance. These changes are consistent with a protective physiologic profile characterized by the lowering of intraglomerular pressure and related cardiorenal risk when adding a sodium-glucose cotransporter 2 inhibitor to conservative therapy. Registration: URL: https://www.clinicaltrials.gov ; Unique identifier: NCT02632747.